Spawning in a cold bath: reproduction of polar and deep‐sea fish family Psychrolutidae. Issue 4 (18th November 2016) - Laptikhovsky, V.; Reid, B.; Brickle, P.
Abstract : This study describes the spawning of the fatheads Psychrolutes marmoratus and Cottunculus granulosus, two psychrolutid species that inhabit the shelf edge and continental slope of the south‐west Atlantic. Females lay large eggs of c. 2·5 mm ( P. marmoratus ) and 4·5–5·0 mm ( C. granulosus ); fecundity is from the hundreds ( C. granulosus ) to a few thousand eggs ( P. marmoratus ). Egg maturation is synchronous in P. marmoratus with an autumn–winter peak of spawning and group‐synchronous in C. granulosus, which reproduces all year round. In the fishery, females predominate among adult fish in both species, possibly indicating male nest guarding on hard grounds inaccessible to fishing vessels. The reproductive strategy of representatives of the Psychrolutidae is similar to that of other sculpins of the superfamily Cottoidea.